How big is the bioenergy piece of the energy pie? Who cares—it's pie!. Issue 9 (24th July 2014) - Somerville, Chris; Youngs, Heather
<x xml:space="preserve">Abstract</x> Biomass supplies more energy around the world today than any other renewable source and has the potential to meet a sizeable portion of future energy demand with substantial greenhouse gas savings and other benefits. The exact contribution will depend on many factors – many of which are political. Rather than calculating and recalculating bioenergy potentials, science should focus on finding the best solutions for sustainable and efficient use, regardless of exactly how big the piece of pie is. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>